New Insight in Etiology of Vitiligo, Association of IncRNA and some Immunological Parameters with Expression of Melanin Concentration Hormone and Sirtuin 1 Genes in Generalized and Segmented Vitiligo - Suleiman, Ahmed (Jordan Medical Journal, 2025)
Background: Long non-coding RNAs (LncRNAs) represent a subset of genetic material exceeding 200 base pairs that lack protein-coding capacity, yet possess the unique capability to modulate gene expression. This study was conducted with the purpose of identifying the expression levels of LncRNA SIRT-1, LncRNA MCH, as well as the serum levels of IL-17, IL-33, and IFNγ in individuals with vitiligo. Furthermore, the investigation aimed to explore the potential correlation between long non-coding RNA and the parameters of study. Methods: The investigation was carried out on a cohort consisting of 30 patients with Generalized Vitiligo (GV) - both treated and untreated, 30 patients with Segmented Vitiligo (SV) - also both treated and untreated, and 25 Healthy Controls (HC). Using ELISA, the serum levels of IL-17, IL-33, IFNγ, SIRT 1, and PMCH were measured. Additionally, a gene expression analysis of long non-coding RNA (LncRNA) SIRT-1 and LncRNA PMCH was conducted in patients with GV and SV in order to shed light on their potential implications in the pathogenesis of vitiligo. Results: LncRNA SIRT-1 expression was significantly higher in GV compared to SV (p=0.030, Mann-Whitney test), with mean expression levels of 2.851 (SE: 1.052) and 0.507 (SE: 0.134), respectively. In contrast, no significant difference in LncRNA MCH expression was observed between the two vitiligo types. Conclusion: After investigation of the association between lncRNA expression of the SIRT1 and MCH genes and their corresponding serum concentrations in vitiligo patients, this research elucidated the dysregulated manifestations of LncRNA SIRT-1 and LncRNA MCH in individuals diagnosed with vitiligo, indicating their potential contributions to the etiology of vitiligo. This mechanism could involve the down regulation of serum SIRT-1 and MCH, as well as the elevation of cytokines. `